e-Module e-Sipa' in Culture-Based Basic Services as a Preventive Effort to Bullying in Students - Hadyan Ramadani; Abdullah Sinring; Akhmad Harum (Indonesian Journal of Learning Education and Counseling)
This study aims to develop a bullying prevention E-Module based on 3S culture (sipakatau, sipakainga, and sipakala'biri) in the form of a service E-Module for BK teachers. The development model used is the ADDIE model with a small group trial on 15 students with subject characteristics, namely grade VII students of SMPN 40 Bulukumba. The validation results showed that the e-module material and media obtained a high level of acceptance. Quantitative descriptive analysis stated that 1) the appearance of the E-Module E-Sipa' is attractive by 95%; 2) the E-Module E-Sipa' is practical to use by 93%; 3) the E-Module E-Sipa' is easy to access by 95%; 4) the language in the E-Module E-Sipa' is easy to understand by 90%; 5) the steps of the E-Module E-Sipa' activities are easy to access and interesting by 90%; 6) the material in the E-Module E-Sipa' is easy to understand by 87%; 7) the material in the E-Module E-Sipa' is in accordance with the needs of students by 98%; and 8) the E-Module E-Sipa' helps students in preventing bullying behavior by 98%. And the results of the practicality test on the E-Module E-Sipa' average percentage of 95% with very practical criteria. So it can be concluded that the E-Module in basic BK services based on culture as a preventive measure of bullying behavior in students can be a tool for BK teachers in preventing bullying behavior in students.